DISTRIBUTION OF DISSOLVED HEAVY METAL Hg AND Pb IN LAMONGAN COASTAL WATERS, INDONESIA - Aliviyanti, Dian; Yona, Defri; Asadi, Muhammad Arif; Putri, Anggi Andrianah; Nabilah, Mariah (Journal of Environmental Engineering and Sustainable Technology, 2023)
Lamongan Regency has a fairly progressive fisheries sector with high fishing activity, such as the fishing industry and ports, especially in the Paciran and Brondong subdistricts. On the other hand, rapid fishing activities can also cause the entry of pollutants such as heavy metals and have the potential to reduce water quality in the area. The aim of this research is to analyze water conditions based on physical and chemical parameters as well as the distribution of dissolved heavy metal Hg and Pb in the fisheries industrial area and port of Lamongan Regency. The research was carried out using a purposive sampling method at seven stations along the waters of both Brondong and Paciran Districts. The data used in this research includes water quality parameters and dissolved heavy metal Hg and Pb. Analysis of heavy metal content was carried out in the laboratory using an Atomic Absorption Spectroscopy (AAS) instrument. The results showed that the heavy metal Hg at all stations was not detected by AAS because its concentration was very low. Meanwhile, the heavy metal Pb shows varying values at all stations with a range of 0.08 mg/L – 1.88 mg/L. The concentration of the heavy metal Pb at most location points has exceeded the limits set by Indonesian Government Regulations. The results of statistical analysis show that there is a relationship between temperature and pH and the concentration of the heavy metal Pb in water.